Three-dimensional virtual bone bank system workflow for structural bone allograft selection: a technical report - Ritacco, Lucas (2013)
Structural bone allograft has been used in bone defect reconstruction during the last fifty years with acceptable results. However, allograft selection methods were based on 2-dimensional templates using X-rays.Thanks to preoperative planning platforms, three dimensional (3D) CT-derived bone models were used to define size and shape comparison between host and donor. The purpose of this study was to describe the workflow of this virtual technique in order to explain how to choose the best allograft using a virtualbone bank system. We measured all bones in a 3D virtual environment determining the best match. The use of a virtual bone banksystem has allowed optimizing the allograft selection in a bone bank, providing more information to the surgeons before surgery.In conclusion, 3D preoperative planning in a virtual environment for allograft selection is an important and helpful tool in order to achieve a good match between host and donor.